A dinâmica familiar e conjugal em famílias de crianças com indicadores de transtorno de déficit de atenção com hiperatividade - TDAH - Wagner, Janaína Kriger (Universidade do Vale do Rio dos Sinos, 2012)
ADHD is one of the most common disorders in childhood and adolescence, with estimated 3 to 5% school children presenting it. Its etiology is still widely debated, and there is no common sense about it. Literature has shown many studies according to which ADHD is a developmental disorder with strong neurobiological influence. On the other hand, the relationship between psychosocial and family factors and the occurrence of ADHD in the offspring has been studied by several authors who point out that family and marital conflicts are bigger in families with children presenting this disorder, although it has not become clear yet whether such conflicts precede or succeed its development in the child. This study aims at analyzing the characteristics of family and marital relationships in families with children with ADHD indicators. In order to do so, a qualitative-exploratory approach was used with case studies. Outcomes have shown dysfunctional and quite conflicted family dynamics. Parental relationships have been characterized by a variety of handling difficulties, perhaps influenced by the couple’s former conflicts, another characteristic that these cases had in common. Other elements to be highlighted are the importance and intensity of transgenerational aspects in the cases studied, which pointed to a continuation of model of family and marital functioning that the parental couples had had in their original families, and that was perpetuated in their new families. The outcomes have been organized in two empirical articles: the first one discusses the family dynamics of children with ADHD indicators; the second one presents a single case study, whose focus was the conjugality in families with children with ADHD.
Keywords: Dinâmica familiar; Dinâmica conjugal; TDAH; Crianças; Family dynamics; Marital dynamics; ADHD; Children; ACCNPQ::Ciências Humanas::Psicologia